IMPLIKASI PENERAPAN PP NOMOR 48 TAHUN 2014 TENTANG TARIF ATAS JENIS PENERAPAN NEGARA BUKAN PAJAK YANG BERLAKU PADA DEPARTEMEN AGAMA STUDI KASUS : KUA KECAMATAN CIBINONG - Muhammad Ikbaludin; Kushandajani .; Wahid Abdurrahman (Journal of Politic and Government Studies, 2016)
THE IMPLICATIONS OF THE IMPLEMENTATION OF THE GOVERNMENT REGULATION NO 48 OF 2014 ON THE TARIFFS OF THE TYPES OF NON-TAX STATE REVENUE THAT IS APPLICABLE TO THE DEPARTMENT OF RELIGIOUS AFFAIRSCASE STUDY: OFFICE OF RELIGIOUS AFFAIRS CIBINONG DISTRICTBY : MUHAMMAD IKBALUDINABSTRACTThe matter of marriage and reconciliation becomes a fundamental problem for the ministry of religious affairs. The expensive cost of the marriage and the gratuities for the regional chief often comes out in the media. The Government publishes the Government Regulation No. 48 of 2014 as a response to the problems happened. The purpose of the Implication of the implementation of the Government Regulation No. 48 of 2014 on the tariffs of the types of non-tax state revenue that is applicable to the department of religious affairs according to the case study of the office of religious affairs in Cibinong district is to find out how the Government Regulation No. 48 of 2014 affects the problems existing in the body of the ministry of religious affairs, especially in terms of marriage, reconciliation involving the regional chief, bureaucracy, and society.The method of research used in this study is a qualitative descriptive study which the primary data are the words and actions. The sources of the data obtained are derived from the primary and secondary data. The informants of this study are selected by the purposive sample method (selection on purpose). The data collection techniques used in this study is interview, documentation, observation.The Implementation of the Government Regulation No. 48 of 2014 is intended to address the existing problems in the ministry of religious affairs, especially the issue of marriage and reconciliation that becomes a fundamental need for the society. The implementation of the Government Regulation No. 48 of 2014 for the regional chief, bureaucracy, and society are to make sure about the cost of the marriage and reconciliation as well as the gratuities for the regional chief in carrying out the marriage outside the office or outside working hours. Furthermore, the implementation of the Government Regulation No. 48 of 2014 also put more steps for people registering their marriage directly to the Office of Religious Affairs (KUA). In addition, the Government Regulation No. 48 of 2014 has no implication towards the gratuities for the regional chief as it becomes the reason why the Government Regulation No. 48 of 2014 is published.Keywords: Regulation, Bureaucracy, Service